The causal relationship model of factors influencing fall prevention behaviors of the elderly in Lopburi Province - wisetkaew, Siriwun; Suwan, Prapapen (Journal of Medical and Public Health Region 4, 2024)
The purposes of this quantitative research were to study the level of fall prevention behaviors of the elderly, to develop a causal relationship structural equation model of factors influencing the fall prevention behaviors of the elderly, and to examine the pathways of influence of causal factors on fall prevention behaviors. The sample consisted of 520 elderly people living in Lopburi Province and were selected by multi-stage sampling method. Data were collected using a 5-rating scale questionnaire with a content validity index between 0.60 - 1.00 and questionnaire reliability index of 0.92. The statistics used for data analysis were percentage, mean, standard deviation, influence path analysis by using a computer program. The results showed that the developed model was consistent with the empirical data (Chi-square = 259.96, df = 133, c2/df = 1.95, Index GFI = 0.91, AGFI = 0.86, RMSEA = 0.042). The direct coefficients of self-efficacy and attitude towards fall prevention in elderly fall prevention behavior were 0.86 and 0.44, respectively and the fall prevention behaviors of the elderly were indirectly influenced by health belief model and social support through self-efficacy and attitude towards fall prevention with the influence coefficients of 0.84 and 0.24, respectively. All variables could explain 65% of the variance in fall prevention behavioral variables. In summary, fall prevention among the elderly should promote self-efficacy awareness and have a positive attitude to prevent falls.